Early Rise of Serum hCG in Gestational Diabetes Mellitus Women With Live Birth Through In Vitro Fertilization Procedure - Wu, Wei; Zhang, Li-Feng; Li, Yi-Ting; Hu, Tian-Xiao; Chen, Dan-Qing; Tian, Yong-Hong (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy. The characteristics of early human chorionic gonadotropin (hCG) levels and the rise pattern in patients with GDM after in vitro fertilization (IVF) are unclear. The present investigation was a retrospective cohort analysis of eligible viable pregnancies achieved through IVF in the authors’ hospital between October 2015 and June 2020. The characteristics of initial hCG concentration and the rise pattern in patients with GDM after IVF, and the difference between those of normoglycemic pregnant women, were explored. Using random-effects models, the preferred pattern to describe the increase in log hCG was a quadratic. When gestational age was within 39 days, the linear model adequately characterized the profile, and the average slope was 0.173, yielding a predicted increase of 1.55 (55%) in 1 day and 3.11 (211%) in 2 days. Absolute hCG values—but not the rate of rise—were significantly higher in double embryo transfers and twin pregnancies. Curves reflecting hCG rise from the GDM and non-GDM groups did not differ substantially. The proportion of patients with low initial hCG values (16 days post-oocyte retrieval <100 mIU/ml) was higher in the GDM group (5% vs. 2.09%), although the difference was not statistically significant. Early hCG rise in pregnant women after IVF—whether GDM or non-GDM—could be characterized by quadratic and linear models. However, hCG values on days 14 and 16 post-oocyte retrieval in the GDM group were lower than those in the non-GDM group, with the exception of twin pregnancies. Low hCG values in early pregnancy may be a clue to help predict GDM in the subsequent gestation period.